Viticulture In Madhya Pradesh: A Review - A. K. Hamilton (AG Volumes, 2021)
In spite of the fact that grapevine may thrive in a variety of climates, it grows best in areas that satisfy particular climatic criteria. Tropical areas are those latitudes between the Tropics of Cancer and Capricorn where grapes may be found in abundance. In recent years, viticulture operations in tropical areas have grown considerably, and nations like Brazil, Venezuela, India, & Thailand situated in tropical and subtropical climates provide quality table grapes, wine, grape juice, and raisins. Global advances in communications technology, as well as in geography, provide tremendous opportunity for developing better ways to disseminate precise viticultural information. A number of helpful instruments for monitoring and controlling vine growth have been developed thanks to recent technology advancements. Precision viticulture, on the other hand, aims to use as many observations as possible to characterize the vineyard's geographic variability at a high resolution as well as provide management suggestions to increase quality, output, and sustainability. The study provides a short overview of Madhya Pradesh's precision viticulture technology state-of-the-art.